Socio-philosophical foundations of legal culture and ways of promoting legal education in society - Kakhkharova Matlyuba Manafovna, Tuychieva Khamida Nabievna (International Journal of Advanced Science and Technology, 2019)
The article provides analytical guidance on the methods and tools of socio-philosophical foundations and directions of the methods of formation of legal culture and legal education in society.